2022
DOI: 10.1155/2022/3128933
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Inflammation: The Tumor-Promoting Immunity in the Early Stages of Tumorigenesis

Abstract: Tumorigenesis is a multistage progressive oncogenic process caused by alterations in the structure and expression level of multiple genes. Normal cells are continuously endowed with new capabilities in this evolution, leading to subsequent tumor formation. Immune cells are the most important components of inflammation, which is closely associated with tumorigenesis. There is a broad consensus in cancer research that inflammation and immune response facilitate tumor progression, infiltration, and metastasis via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 143 publications
0
7
0
Order By: Relevance
“…Numerous studies have demonstrated that infiltrating immune cells in the microenvironment exert dual effects of promoting tumor and antitumor growth [18, 19]. On account of the destruction of blood‒brain barrier integrity by gliomas and the lymphatic outflow channels, the immune system can communicate with cells within the central nervous system [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that infiltrating immune cells in the microenvironment exert dual effects of promoting tumor and antitumor growth [18, 19]. On account of the destruction of blood‒brain barrier integrity by gliomas and the lymphatic outflow channels, the immune system can communicate with cells within the central nervous system [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…TPICs chiefly comprise regulatory T cells (Tregs) and myeloid-derived suppressor cells. Tumor-related immune cells improve tumor development by secreting cytokines and promoting metastasis through the production of growth factors and matrix-degrading enzymes ( Bi et al, 2022 ). Immune infiltration could also influence the clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated immune cells can promote tumor progression by producing cytokines and assist tumor metastasis by secreting growth factors or matrix-degrading enzymes ( 43 ). Our study found that the SLFN5, SLFN11, SLFN12, SLFN12L, and SLFN14 expressions were positively linked with the infiltration of CD8 + T cells CD4 + T cells, macrophages, neutrophils, and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%